АКТУАЛЬНЫЕ ПРОБЛЕМЫ В РАБОТЕ С МУЗЫКАЛЬНО-ОДАРЕННЫМИ СТУДЕНТАМИ И ЭФФЕКТИВНЫЕ МЕТОДЫ ИХ ОБУЧЕНИЯ - Лопарева, Ю.В.; Бактыгалиева, А.К.; Усенова, Г.Р. (My University, 2019)
Аннотация В работе рассматриваются актуальные проблемы в работе с одаренными студентами, вопрос об эффективности различных методов обучения. Abstract The following job offers address current issues in working with gifted students. The following sentence as well as the question of the effectiveness of various teaching methods
Actual problems in working with musically gifted student’s effective methods of their learning
Keywords: одаренность; талант; гениальность; творческая личность; сотрудничество; мотивация